2019
DOI: 10.3390/biom9110654
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cardiac Biomarkers for Monitoring Improvement of Left Ventricular Function by Immunoadsorption Treatment in Dilated Cardiomyopathy

Abstract: Immunoadsorption and subsequent administration of intravenous immunoglobulin (IVIG) have shown beneficial effects on cardiac function and symptoms in patients with dilated cardiomyopathy. Biomarkers play an emerging role in disease monitoring and outcome prediction of heart failure (HF) patients. We aimed to analyze cardiac biomarkers as predictor for improvement of left ventricular (LV) function after immunoadsorption treatment in dilated cardiomyopathy (DCM). Thirty-one patients with dilated cardiomyopathy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Fourteen studies evaluating the diagnosis and/or management of ICM formed the final dataset for analysis in the present meta-analysis [193][194][195][196][197][198][199][200][201][202][203][204][205][206]. Eight (8) of the studies were randomized prospective clinical trials [196,197,[199][200][201][202][203]206] and the remaining were non-randomized prospective or retrospective studies [193][194][195]198,204,205]. In total, the 14 studies enrolled 503 patients suspected with MC with cardiac involvement or ICM.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies evaluating the diagnosis and/or management of ICM formed the final dataset for analysis in the present meta-analysis [193][194][195][196][197][198][199][200][201][202][203][204][205][206]. Eight (8) of the studies were randomized prospective clinical trials [196,197,[199][200][201][202][203]206] and the remaining were non-randomized prospective or retrospective studies [193][194][195]198,204,205]. In total, the 14 studies enrolled 503 patients suspected with MC with cardiac involvement or ICM.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, studies revealed beneficial effects of IA therapy in improving cardiac function and clinical outcomes in DCM patients. Recent studies have also shown that IA therapy can facilitate remodeling of left ventricle [23] …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that IA therapy can facilitate remodeling of left ventricle. [23] The main pathological character of DCM is the remodeling of cardiac chambers. Ventricular remodeling is a dynamic process.…”
Section: Discussionmentioning
confidence: 99%
“…First described in 1969, immunoadsorption (IA) has been widely utilized in the treatment of various neurological, cardiac, and rheumatological diseases [13][14][15]. In plasmapheresis, the plasma is discarded, whereas in IA, it is passed through an adsorption column that specifically depletes immunoglobulins and immune complexes [16].…”
Section: Color Version Available Onlinementioning
confidence: 99%